DEFENSE MECHANISM AMONG INDONESIAN MOSLEMS COMMUNITY IN THE COVID-19 ERA - Muhamad Irfan Dzihni (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Introduction – COVID-19 has been a stressor to the general population, include the religious community. The coping mechanism came into many forms.The one mechanism among Indonesian moslems community seems to be disbenefecial, which sign is a denial of COVID-19 protocol and religious explanation. Here, we conclude the reaction according the theory of psychodynamics. Methods – Researcher review 9 journals and 3 books around the topics defense mechanisms, Indonesian islamic disobeying community, and rationalization. Results – The behaviour the moslem community present can be divided as obeying the rules and the opposite. propitiously, the majority of the communtiy tend to implement the regulation ruled. The rule-disobeying manners come into many forms, as appeared the anti-science community labelling the credence to science as a disbelief of god (syirk). Some came as an anti-vaccine community. Discuss – The use of disavowal may protect individuals from their awareness relating to their behaviours, but not effectively hide them from others. Rationalization is the most prevalent defenses in all personality disorders examined (schizotypal, borderline, antisocial, and narcissistic). Conclusion – Among Indonesians that are moslems in the era of pandemics, there are populations using rationalization to cope with the problems correlate to COVID-19 protocols. They tend to normalize the behaviour utilizing religious topics, such as the trust of faith than science. Rationalization is a disavoal of hierarchy of defense mechanisms. It can benefit physiologically relating to their rule-violating behaviour, but amidst pandemics, this is nonprovitable to self-biological health and social environment. Keywords: psychodynamic, defense mechanism, moslem, Indonesia.